DUAL SITUATED LEARNING MODEL AS REMEDIAL TEACHING TO ACID-BASE MISCONCEPTIONS - Mela Yuliyanti; Sulistyo Saputro; Ashadi Ashadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
The research aimed to determine whether or not there is an acid-base misconception using a three-tier multiple choice and the effectiveness of using DSLM in reducing these misconceptions. The research design is descriptive qualitative research with a case study approach. The sampling technique used purposive sampling so that the sample is a student of class XI MIPA 1 and XI MIPA 5. The data collection technique was through three-tier multiple-choice, learning with DSLM, and interviews. After the first TTMC test, the researcher conducted remedial teaching with DSLM to improve the acid-base misconception. The results of the research showed that as many as 29 of 61 students had misconceptions about different sub-concepts. Most of the students had misconceptions about such characteristics of acid-base solutions, acid-base theories, pH concepts, the strength of acids and bases, the electrolytes of acid and base solutions, and neutralization reactions. After the researcher did DSLM learning, there was a decrease in misconceptions from 48.14% to 27.02% (low-misconceptions category). It shows that DSLM can be enough effective strategy to reduce student misconceptions.AbstrakPenelitian ini bertujuan untuk mengetahui ada atau tidaknya miskonsepsi asam basa menggunakan three-tier multiple choice dan efektivitas penggunaan DSLM dalam mereduksi miskonsepsi tersebut. Desain penelitian merupakan penelitian kualitatif deskriptif dengan pendekatan studi kasus. Pengambilan sampel menggunakan teknik purposive sampling sehingga didapat siswa kelas XI MIPA 1 dan MIPA 5. Teknik pengumpulan data melalui hasil three-tier multiple choice, pembelajaran DSLM dan wawancara. Setelah uji TTMC pertama, dilakukan remedial teaching dengan DSLM untuk memperbaiki konsep asam basa yang menjadi miskonsepsi. Hasil penelitian menunjukkan sebanyak 29 dari 61 siswa mengalami miskonsepsi pada sub konsep yang berbeda-beda. Sub konsep tersebut ialah karakteristik larutan asam basa, teori asam basa, kekuatan asam dan basa, derajat keasaman (pH), keelektrolitan larutan asam dan basa, serta reaksi netralisasi. Setelah melakukan pembelajaran DSLM, terjadi penurunan miskonsepsi dari 48,14% menjadi 27,02% (kategori miskonsepsi rendah). Hal ini menunjukkan bahwa DSLM dapat menjadi strategi yang cukup efektif dalam mereduksi miskonsepsi siswa.How To Cite: Yuliyanti, M., Saputro, S., Ashadi. (2022). Dual Situated Learning Model as Remedial Teaching to Acid-Base Misconceptions. EDUSAINS, 14 (2) : 174-187